DEVELOPING SPEAKING SKILLS IN ENGLISH LEARNERS - Jumaboyeva Oʻgʻiloy Yaxshilik qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Speaking skills are a fundamental component of language proficiency and play a crucial role in effective communication. Developing speaking abilities in English learners remains a challenge due to anxiety, lack of practice, and limited exposure to authentic communication. This article examines strategies and methods for enhancing speaking skills among English learners, including communicative activities, role-plays, games, and collaborative tasks. The study highlights the importance of teacher guidance, learner motivation, and interactive classroom environments. Findings indicate that consistent practice, feedback, and learner-centered approaches significantly improve speaking proficiency (Harmer, 2007; Thornbury, 2005).